2020
DOI: 10.1016/j.bone.2020.115457
|View full text |Cite
|
Sign up to set email alerts
|

The risk of hip and non-vertebral fractures in type 1 and type 2 diabetes: A systematic review and meta-analysis update

Abstract: BackgroundDiabetes is associated with increased fracture risk but we do not know what affects this risk. We investigated the risk of hip and non-vertebral fractures in diabetes and whether Diabetes is associated with an increase in both hip and non-vertebral fracture risk. HighlightsThe risk of hip fractures was greater in T1D than T2D Hip fracture risk is higher in in people younger than 65 years for both type 1 and type diabetesIn type 2 diabetes, insulin use and longer diabetes duration is associated with g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
92
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(101 citation statements)
references
References 101 publications
(163 reference statements)
5
92
0
4
Order By: Relevance
“…In addition, type 2 diabetes, which frequently coexists with obesity, may further impact fracture risk. Indeed, many studies reported increased risk of hip and non-vertebral fracture in individuals with type 2 diabetes [ 19 , 192 ]. However, studies considering presence of type 2 diabetes in the association between obesity and fracture risk are limited: most studies used type 2 diabetes as an adjustment factor and did not assess whether the presence of type 2 diabetes modifies the association between obesity and fracture incidence.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, type 2 diabetes, which frequently coexists with obesity, may further impact fracture risk. Indeed, many studies reported increased risk of hip and non-vertebral fracture in individuals with type 2 diabetes [ 19 , 192 ]. However, studies considering presence of type 2 diabetes in the association between obesity and fracture risk are limited: most studies used type 2 diabetes as an adjustment factor and did not assess whether the presence of type 2 diabetes modifies the association between obesity and fracture incidence.…”
Section: Discussionmentioning
confidence: 99%
“…In der 2. Metaanalyse [ 40 ] wurden 49 Studien mit insgesamt mehr als 17 Mio. Teilnehmern und 319.652 Hüftfrakturen und knapp 3 Mio.…”
Section: Endokrinologieunclassified
“…The meta-analyses that evaluated the fracture risk in T2DM patients are summarized in Table 1 . Among the skeletal sites, increased risk of hip fracture (8%-70%) has been reported consistently in most of the meta-analyses[ 14 , 39 - 42 ]. Young age, prolonged duration of diabetes, use of insulin[ 39 ] and Asian ethnicity[ 40 ] are the factors that have been associated with a higher risk of hip fracture in diabetic patients.…”
Section: Bone Health In T2dmmentioning
confidence: 99%